Unmet needs for modern contraceptive methods among sexually active adolescents and young women in Togo: a nationwide cross-sectional study - Smaila Alidou; Smaila Alidou; Lucien Désiré Dahourou; Lucien Désiré Dahourou; Ter Tiero Elias Dah; Armel Sogo; Tchasso Serge Kenao; Dègninou Yehadji; Nicolas Meda; Didier Koumavi Ekouevi (Frontiers in Public Health, 2023)
BackgroundThe unmet need for modern contraceptives among sexually active adolescent and young women (AYW) in Africa contributes to high morbidity and mortality. To investigate the prevalence of unmet need for modern contraceptives and its associated factors among AYW in Togo, we performed a secondary analysis of data from the MICS-62017 survey.MethodWe extracted data from sexually active AYW aged 15–24  years for the analysis and used multi-level logistic regression models to identify factors associated with unmet need for modern contraceptives.ResultsAmong the AYW, the median age was 20  years. The prevalence of unmet need for modern contraceptives was 27.02%. Factors that increased the likelihood of having unmet need for contraceptives included being in the “Poor” or “Middle” quintile of household wealth, aged 20–24  years, and completing primary or secondary education. Living in a household headed by a woman and having a household head aged 19–38, 39–58, or greater than 78  years decreased the likelihood of unmet need for modern contraceptives.ConclusionThe study highlights the high-unmet need for modern contraceptives among sexually active AYW in Togo and emphasizes the importance of addressing individual and household/community factors to improve their sexual and reproductive health. Interventions such as increasing AYW awareness, providing social marketing campaigns in schools, and targeting men-headed households could help promote modern contraceptive use and improve the sexual and reproductive health of AYW in Togo.